3.2 mΩcm2 enhancement‐mode GaN MOSFETs with breakdown voltage of 800 V. Issue 5 (29th March 2016) - Saito, Hisashi; Yumoto, Miki; Fukatsu, Shigeto; Kajiwara, Yosuke; Shindome, Aya; Oasa, Kohei; Takada, Yoshiharu; Tsuda, Kunio; Kuraguchi, Masahiko
Abstract: Enhancement‐mode GaN metal‐oxide‐semiconductor field‐effect transistors (MOSFETs) have been reported. We utilized the atomic layer deposition (ALD) method for the fabrication process of the gate dielectric, in order to suppress plasma damage and obtain high‐quality dielectric film. In the fabricated devices, the specific on‐state resistance of 3.2 mΩcm 2 and the breakdown voltage of 800 V were achieved. Moreover, a 10‐year lifetime with a cumulative failure rate of 0.1% was guaranteed at over 20 V. This voltage was twice the operation voltage of 10 V. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)